Marginal Zone B-Cell Lymphoma of the Lacrimal Gland Secondary to Sjogren’s Syndrome - Hatice Deniz İlhan; Elif Betül Türkoğlu; Ahmet Burak Bilgin; Bahar Akkaya; Mustafa Ünal (Türk Oftalmoloji Dergisi, 2014)
Sjogren’s syndrome is a chronic, autoimmune, inflammatory disease which can affect all exocrine glands, particularly the salivary and lacrimal glands, causing dryness of the mouth and eyes. The most serious complication is the development of lymphoma. In this article, we aimed to present a very rare case of marginal zone B-cell lymphoma in the lacrimal gland secondary to Sjogren’s syndrome. (Turk J Ophthalmol 2014; 44: 322-4)